Allele-specific methylation of SPDEF: a novel moderator of psychosocial stress and substance abuse - Tay, Nicole; Banaschewski, Tobias; Flor, Herta; Nees, Frauke; Hohmann, Sarah (The American journal of psychiatry, 2019)
Objective:Psychosocial stress is a key risk factor for substance abuse among adolescents. Recently, epigenetic processes such as DNA methylation have emerged as potential mechanisms that could mediate this relationship. The authors conducted a genome-wide methylation analysis to investigate whether differentially methylated regions are associated with psychosocial stress in an adolescent population.Methods:A methylome-wide analysis of differentially methylated regions was used to examine a sample of 1,287 14-year-old adolescents (50.7% of them female) from the European IMAGEN study. The Illumina 450k array was used to assess DNA methylation, pyrosequencing was used for technical replication, and linear regression analyses were used to identify associations with psychosocial stress and substance use (alcohol and tobacco). Findings were replicated by pyrosequencing a test sample of 413 participants from the IMAGEN study.Results:Hypermethylation in the sterile alpha motif/pointed domain containing the ETS transcription factor (SPDEF) gene locus was associated with a greater number of stressful life events in an allele-dependent way. Among individuals with the minor G-allele, SPDEF methylation moderated the association between psychosocial stress and substance abuse. SPDEF methylation interacted with lifetime stress in gray matter volume in the right cuneus, which in turn was associated with the frequency of alcohol and tobacco use. SPDEF was involved in the regulation of trans-genes linked to substance use.Conclusions:Taken together, the study findings describe a novel epigenetic mechanism that helps explain how psychosocial stress exposure influences adolescent substance abuse.
Published:11 Dec 2018
Gesehen am 09.05.2019